2013
DOI: 10.1097/igc.0b013e318285a4b2
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cervical Human Papillomavirus Infection and High-Grade Intraepithelial Lesion in Women Aged 20 to 31 Years in Germany

Abstract: Although the study was hampered by its relatively small sample size, our data suggest that main risk factors for the acquisition of HPV infection are a higher number of sexual partners and younger age, whereas older age and genital warts may be epidemiological cofactors in the development of HSIL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 40 publications
3
24
0
2
Order By: Relevance
“…It has been shown that active smoking or young age at sexual debut are associated with a higher number of sexual partners [19,20]. It is important to note, however, that factors associated with the presence of HPV infection may not be identical with factors associated with a risk of developing cervical abnormalities [21]. Genotype of infection, viral load, and individual health conditions might contribute to a higher risk of cervical precancer and cancer as well [22-27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that active smoking or young age at sexual debut are associated with a higher number of sexual partners [19,20]. It is important to note, however, that factors associated with the presence of HPV infection may not be identical with factors associated with a risk of developing cervical abnormalities [21]. Genotype of infection, viral load, and individual health conditions might contribute to a higher risk of cervical precancer and cancer as well [22-27].…”
Section: Discussionmentioning
confidence: 99%
“…For women who are considered at high risk of HPV infection (e.g. HIV-infected women or women who engage in sexual risk behaviours such as a higher number of partners)11 12 or those who cannot access routine screening, self-collection of vaginal samples can lead to increased screening 13…”
Section: Introductionmentioning
confidence: 99%
“…9 Many studies have also suggested that women with multiple sexual partners are at high risk for HPV acquisition and cervical cancer. 10 The number of live births is a consistent risk factor for cervical cancer. There is a linear trend in the association between parity and risk.…”
Section: Introductionmentioning
confidence: 99%